EFEKTIFITAS PENERAPAN E-COURT DALAM PENYELESAIAN PERKARA (Studi Kasus di Pengadilan Agama Painan) - Pebrianto, Roni; Ikhwan, Ikhwan; Azwar, Zainal (Jurnal AL-AHKAM, 2021)
This research is motivated by the application of e-Court at the Painan Religious Court. The aim is to modernize the administration of cases and trials to overcome obstacles in the process of judicial administration and to provide convenience for the public to litigate cases in court. However, the facts on the ground are that the people with litigation have not felt the ease of implementing the e-Court because there are so many obstacles that have occurred, so that the litigants find it difficult to proceed in an e-Court case. The formulation of the problem in this study, namely; How is the application of e-Court in the settlement of cases at the Painan Religious Court, what are the factors that cause problems in the application of e-Court in solving cases at the Painan Religious Court and what are the efforts made by the Painan Religious Court to overcome obstacles in the application of eCourt in case resolution. This research is a field research (field research) using qualitative descriptive research methods. The data sources of this research are primary data and secondary data. The technique of collecting data in this research is by making observations, interviews and documentation. This research was conducted at the Painan Religious Court with sources as the Head of the Painan Religious Court, the clerk of the Painan Religious Court, e-Court officers and the public with litigation at the Painan Religious Court. The results of the study concluded that; 1) The application of e-Court in case resolution has been enforced at the Painan Religious Court but has not been effective. 2) Factors causing obstacles to the application of e-Court in solving cases at the Painan Religious Court can be categorized as; internal factors, namely no direct face-to-face socialization to the community, inadequate facilities and infrastructure, unpreparedness of human resources, incomplete application menus and external factors in the form of technology failure, no internet access in most areas of South Coastal District, no email, do not have an android mobile phone and do not have a personal account.